RSA authentication mechanisms in control grid computing environment using Gridsim toolkit - Ismail, Saiful Adli; Ngadi, Md Asri; Mohd Sharif, Johan; Kama, Mohd Nazri; Sarkan, Haslina (2015)
There are security concerns when our sensitive data is placed in the third party infrastructure such as in the Grid Computing environment. As such, it is difficult to be assured that our data is in the safe hands.Thus, authentication has become the most critical factor pertaining to this.There are several approaches has been discussed in the grid computing environment on the safeguard, scalable and efficient authentication that are either Virtual Organization centric or Resource centric.Most of the grid computing uses public key infrastructure (PKI) to secure the identification, but the vulnerability are still cannot be avoid. In order to satisfy the security need of grid computing environment, we design an alternative authentication mechanism using RSA algorithm to ensure the user identification, and carry out the experiment in the Gridsim toolkit simulator.